Orally administered boldine reduces muscle atrophy and promotes neuromuscular recovery in a rodent model of delayed nerve repair - Burrell, Justin C.; Vu, Phuong T.; Alcott, Owen J. B.; Toro, Carlos A.; Cardozo, Christopher; Cullen, D. Kacy (Frontiers in Cellular Neuroscience, 2023)
Peripheral nerve injury often results in poor functional recovery due to a prolonged period of muscle denervation. In particular, absent axonal contact, denervated muscle can undergo irrevocable atrophy and diminished receptiveness for reinnervation over time, ultimately reducing the likelihood for meaningful neuromuscular recovery. While innovative surgical approaches can minimize the harmful effects of denervation by re-routing neighboring – otherwise uninjured – axons, there are no clinically-available approaches to preserve the reinnervation capacity of denervated muscles. Blocking intramuscular connexin hemichannel formation has been reported to improve muscle innervation in vitro and prevent atrophy in vivo. Therefore, the current study investigated the effects of orally administered boldine, a connexin hemichannel inhibitor, on denervated-related muscle changes and nerve regeneration in a rat model of delayed peripheral nerve repair. We found that daily boldine administration significantly enhanced an evoked response in the tibialis anterior muscle at 2 weeks after common peroneal nerve transection, and decreased intramuscular connexin 43 and 45 expression, intraneural Schwann cell expression of connexin 43, and muscle fiber atrophy up to 4 weeks post transection. Additional animals underwent a cross nerve repair procedure (tibial to common peroneal neurorrhaphy) at 4 weeks following the initial transection injury. Here, we found elevated nerve electrophysiological activity and greater muscle fiber maturation at 6 weeks post repair in boldine treated animals. These findings suggest that boldine may be a promising pharmacological approach to minimize the deleterious effects of prolonged denervation and, with further optimization, may improve levels of functional recovery following nerve repair.